A new Urartian temple in Körzüt fortress, Turkey: a report on the rescue excavation of 2016 and new approaches on the origin of Urartian square temple architecture - Kuvanç, Rıfat; Işık, Kenan; Genç, Bülent (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
In this article we share the results of a rescue excavation carried by the Van Museum at Körzüt fortress in 2016. During excavations on the south-west side of Körzüt fortress which was the most important centre of the Urartian Kingdom in the Muradiye plain according to the Urartian inscriptions and the discovered architectural remains, our research team reached the ruins of a square-planned room with a rabbeted façade. Although it is similar to the standard square-planned Urartian temples, especially with its rabbeted façade and square-planned cella, this structure appears as a new example in the light of its external plan that can be determined. Although there is no building inscription, the existence of a rabbeted façade that we know only from the temple structures in Urartian architecture, shows that this building is a temple. This structure, which we think belongs to the early period of the Urartian Kingdom in terms of both stonework and plan, also allows us to make new contributions to the discussions regarding the origin and development of the Urartian religious architecture. In terms of its external plan, it has a rectangular form and a square cella similar to the Neo-Hittite temples found in Northern Syria and Levantine region. Except for the Urartian period, which is emphasized in the article, the potsherds mostly belonging to the Middle Ages and a coin that belongs to the 10th or 11th century AD are other important small finds.